2014
DOI: 10.3758/s13421-014-0421-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental support and secondary tasks on visuospatial working memory

Abstract: The present experiments examined the effects of environmental support on participants’ ability to rehearse locations and its role in the effects of secondary tasks on memory span. In Experiment 1, the duration of inter-item intervals and the presence of environmental support for visuospatial rehearsal (i.e., the array of possible memory locations) during the inter-item intervals were both manipulated across four tasks. When support was provided, memory spans increased as the inter-item interval durations incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 39 publications
6
48
2
Order By: Relevance
“…This evidence is consistent with the idea that gazes during retention reflect attempts to keep the spatial list in mind, analogously to using speech to support memory for verbal information. Other evidence is likewise consistent with the hypothesis that overt fixations toward to-be-remembered spatial positions boost memory (e.g.,; Guérard & Tremblay, 2011;Guérard, Tremblay, & Saint-Aubin, 2009;Lilienthal, Hale, & Myerson, 2014), although overt fixations are apparently of limited use for supporting recall compared to covert oculomotor planning (Godijn & Theeuwes, 2013;Pearson, Ball, & Smith, 2014).…”
Section: Introductionsupporting
confidence: 66%
“…This evidence is consistent with the idea that gazes during retention reflect attempts to keep the spatial list in mind, analogously to using speech to support memory for verbal information. Other evidence is likewise consistent with the hypothesis that overt fixations toward to-be-remembered spatial positions boost memory (e.g.,; Guérard & Tremblay, 2011;Guérard, Tremblay, & Saint-Aubin, 2009;Lilienthal, Hale, & Myerson, 2014), although overt fixations are apparently of limited use for supporting recall compared to covert oculomotor planning (Godijn & Theeuwes, 2013;Pearson, Ball, & Smith, 2014).…”
Section: Introductionsupporting
confidence: 66%
“…In a single experimental session that lasted approximately 1.5 hours, each participant performed four conditions of a visuospatial simple span task (see Figure 1) that were largely identical to the task conditions used by Lilienthal et al (2014) in their Experiment 1. In each of the four conditions, participants were shown an array of 30 circles on a computer screen.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, Lilienthal et al (2014) investigated whether visuospatial rehearsal, and thus visuospatial memory, was affected by the presence or absence of environmental support during inter-item intervals. In two experiments, when environmental support was present (i.e., participants viewed the array of possible locations during inter-item intervals), young adults’ memory spans were significantly larger with long (4.0 s) inter-item intervals than with short (1.0 s) intervals, whereas when environmental support was absent (i.e., participants viewed a blank screen during inter-item intervals), memory spans were significantly smaller with long inter-item intervals.…”
mentioning
confidence: 99%
“…Hence, at least for verbal memoranda, whether or not memory declines over a filled RI depends on the variability of distractor processing (see Figure 7). At the same time, some studies using visual or spatial memoranda have found that extending the duration of the RI impairs memory even in the absence of a concurrent processing task (B3; Lilienthal, Hale, & Myerson, 2014;Mercer & McKeown, 2014;Ricker & Cowan, 2010).…”
Section: Round B: Retention Interval and Distractor Processingmentioning
confidence: 99%